2006
DOI: 10.1111/j.1365-2125.2006.02619.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term and concentration‐dependent beneficial effect of efavirenz on HDL‐cholesterol in HIV‐infected patients

Abstract: Aims To investigate the long‐term effects of efavirenz on cholesterol (TC), high‐density lipoprotein cholesterol (HDL‐C), low‐density lipoprotein (LDL‐C) and triglycerides (TG). Methods Thirty‐four HIV‐infected patients who commenced efavirenz therapy were monitored for 36 months. Results In patients with baseline HDL‐C < 40 mg · dL−1 an increase in HDL‐C from 31 ± 1 mg · dL−1 to 44 ± 2 mg · dL−1 (95% confidence interval 5.9, 21.9, P < 0.01) was observed and remained throughout the follow‐up period. Median efa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 5 publications
1
22
0
Order By: Relevance
“…Most of the published studies on this issue concur in showing a negative impact of protease inhibitors (PI) on lipid profile and on cardiovascular risk, particularly with the use of ritonavir as a pharmacological booster, and a better lipid or risk profile associated to use of non-nucleoside reverse transcriptase inhibitors (NNRTIs), particularly nevirapine. 1,3,[6][7][8][9][10][11][12][13][14][15] In recent years, some information became available on the lipid profile of HIV-positive pregnant women receiving antiretroviral treatment. We previously showed, on a background of a progressive increase in plasma triglyceride and cholesterol levels during pregnancy, an additional and independent effect of protease inhibitors in increasing triglyceride levels at all pregnancy trimesters.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the published studies on this issue concur in showing a negative impact of protease inhibitors (PI) on lipid profile and on cardiovascular risk, particularly with the use of ritonavir as a pharmacological booster, and a better lipid or risk profile associated to use of non-nucleoside reverse transcriptase inhibitors (NNRTIs), particularly nevirapine. 1,3,[6][7][8][9][10][11][12][13][14][15] In recent years, some information became available on the lipid profile of HIV-positive pregnant women receiving antiretroviral treatment. We previously showed, on a background of a progressive increase in plasma triglyceride and cholesterol levels during pregnancy, an additional and independent effect of protease inhibitors in increasing triglyceride levels at all pregnancy trimesters.…”
Section: Introductionmentioning
confidence: 99%
“…5 Therapy with nonnucleoside reverse transcriptase inhibitor (NNRTI)-based regimens using nevirapine (NVP) or efavirenz (EFV) has been reported to cause modest increases in LDL-C, non-highdensity lipoprotein cholesterol (non-HDL-C), and TG, but also a striking and potentially favorable increase in HDL-C levels. [6][7][8][9] We assessed changes in fasting metabolic (TC, HDL-C, directly measured LDL-C, TG, insulin, glucose, and lactate) parameters and in body circumference indices (waist, hip, midarm, and midthigh) after initiation of PI-sparing regimens within AIDS Clinical Trials Group (ACTG) study 5095, a multicenter ARV trial in treatment-naive subjects conducted by the ACTG. The patients were randomized into 1 of 3 regimens consisting of EFV in combination with zidovudine (ZDV) and lamivudine (3TC) with or without abacavir (ABC) or an all-nucleoside regimen of ZDV/3TC/ABC.…”
mentioning
confidence: 99%
“…In addition, it has been shown that alterations in HDL structure and composition can affect PON-1 activity and function [26]. The effect of HIV infection on HDL metabolism is well documented [8], and we have previously shown that EFV is associated with higher values of HDL-c [21]. Thus the alterations of HDL-c caused by EFV could be stabilizing the link of the enzyme to HDL, hence allowing higher enzymatic activity.…”
Section: Discussionmentioning
confidence: 90%
“…The association of PON-1 activity with EFV concentrations is important to distinguish if the effect relies on the response to treatment or on EFV per se. Nevertheless, excluding NNRTI [21,36], the majority of antiretroviral drugs have been described as not affecting HDL-c [2,7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation